Lobectomy with ECMO Support in an Infant Who Developed Pulmonary Interstitial Emphysema Following Repair of Hypoplastic Aortic Arch - Michael Magarakis (Brazilian Journal of Cardiovascular Surgery)
Abstract Pulmonary interstitial emphysema (PIE) is a common problem in premature neonates with respiratory distress syndrome. This condition is often related to barotrauma caused by mechanical ventilation or continuous positive airway pressure applied to low birth weight neonates. The clinical diagnosis can be challenging. However, after proper diagnosis, several interventions are available for successful management. We describe an infant who developed severe PIE with recurrent pneumothoraces and development of a persistent bronchopleural fistula shortly after repair of a hypoplastic aortic arch and description of successful lobectomy with the assistance of extracorporeal support (ECMO).